Experimental characterisation of CO2 + C6F6 mixture: Thermal stability and vapour liquid equilibrium test for its application in transcritical power cycle. (25th July 2022) - Di Marcoberardino, G.; Morosini, E.; Di Bona, D.; Chiesa, P.; Invernizzi, C.; Iora, P.; Manzolini, G.
Highlights: Analysis of CO2 blend as working fluid in transcritical cycle for CSP application. Experimental vapour liquid equilibrium measurements. Equation of state calibration with VLE data. Maximum operating temperature identified through thermal stability test. Preliminary thermodynamic assessment of the power cycle. Abstract: Nowadays supercritical CO2 cycles are considered as a promising alternative to the traditional steam cycle for the power block in CSP plants with the aim of enhancing the system efficiency and reducing costs. This work deals with the experimental characterisation of a CO2 blend as working fluid in transcritical cycle: the addition of C6 F6 as a dopant increases the fluid critical temperature allowing for a condensing cycle in hot environment with ambient temperature higher than 40 °C. The potential benefits on adopting this mixture passes through thermal stability test for identifying its maximum operating temperature and Vapour Liquid Equilibrium measurements for tuning the Equations of State, thus having a good prediction of the thermodynamic properties. The static method with thermal stress test at different operating temperatures shows that the mixture can withstand to about 600 °C in an Inconel 625 vessel. Furthermore, the standard Peng-Robinson with the optimised binary interaction parameter is selected for a preliminary thermodynamic assessment of the power cycle. An efficiency of 41.9% is found for an optimum mixture composition with a CO2 molar content of 84% considering a turbine inlet pressure of 250 bar and a maximum and minimum cycle temperature of 550 °C and 51 °C respectively.